Marketing strategy formulation of take a bowl - Putri Ramadhani, Retno; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2019)
Abstract - A food business in Jakarta offers many types of food. Take a Bowl is Indonesian rice bowl, located at a food court which close to a University. It joins as a merchant on ojek online named Gojek to sell the product. Many people still unaware of it, but it lacks of promotion and offers customized menu that is inefficiency for company. This research is using questionnaire which divided in two aspects for offline and online. It uses Five C’s which company is part of internal environment and the remains of it are explain external environment. CPM which uses to compare Take a Bowl with several competitors and appraised by the owners and employee. Moreover, it used STP and Marketing Mix which explains the current situation of Take a Bowl. All those tools generate to SWOT Analysis. As the result, Take a Bowl is the worst compared with the competitors and lack of activities to attract customers. Proposing the new marketing strategy helps company performance which use STP and Marketing Mix as the tools. Afterwards, Take a Bowl should change in more variety way and more attractive. The next plan is to open new branch near colleges and renew the menu with the prices adjusted to it. Take a Bowl will be done some promotion activities which will be scheduled well as implementation plan. This implementation plan will be implemented for the next two years which is intermediate term. A food business is turbulence depend on its trend. Keywords: Marketing Strategy, Food Business, STP, Marketing Mix